Banhatti, revan and hyper-indices of silicon carbide Si2C3-III[n,m] - Zhao Dongming (De Gruyter, 2021)
In recent years, several structure-based properties of the molecular graphs are understood through the chemical graph theory. The molecular graph GG of a molecule consists of vertices and edges, where vertices represent the atoms in a molecule and edges represent the chemical bonds between these atoms. A numerical quantity that gives information related to the topology of the molecular graphs is called a topological index. Several topological indices, contributing to chemical graph theory, have been defined and vastly studied. Recent inclusions in the class of the topological indices are the K-Banhatti indices. In this paper, we established the precise formulas for the first and second K-Banhatti, modified K-Banhatti, K-hyper Banhatti, and hyper Revan indices of silicon carbide Si2C3{{\rm{Si}}}_{2}{{\rm{C}}}_{3}-III[n,m]{\rm{III}}\left[n,m]. In addition, we present the graphical analysis along with the comparison of these indices for Si2C3{{\rm{Si}}}_{2}{{\rm{C}}}_{3}-III[n,m]{\rm{III}}\left[n,m].